2007
DOI: 10.1097/cad.0b013e3282ef532d
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 antagonist, geldanamycin, inhibits proliferation, induces apoptosis and blocks migration of rhabdomyosarcoma cells in vitro and seeding into bone marrow in vivo

Abstract: In this study, geldanamycin (GA) was found to have an antiproliferative effect on both embryonal and alveolar rhabdomyosarcoma (RMS) cell lines. The maximum level of inhibition reached 80% for both embryonal and alveolar RMS. After GA treatment, cells also became apoptotic as judged by Annexin V-positive staining, activation of caspase-3 pathway and poly(ADP ribose) polymerase cleavage. GA was responsible for the arrest of RMS cells in both G1 and G2/M phases of the cell cycle. G1 blockade, however, was transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…This block of tumor cell migration is due to inhibition of MET receptor expression (mRNA expression and FACS analysis in this study). Similar results have been obtained for different tumors (19,22,23,28). GAs are able to inhibit the expression of MAPK and AKT kinases which were shown previously to be involved in activating the motility of tumor cells (26,27).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This block of tumor cell migration is due to inhibition of MET receptor expression (mRNA expression and FACS analysis in this study). Similar results have been obtained for different tumors (19,22,23,28). GAs are able to inhibit the expression of MAPK and AKT kinases which were shown previously to be involved in activating the motility of tumor cells (26,27).…”
Section: Discussionsupporting
confidence: 87%
“…In our previous studies on rhabdomyosarcoma cells we showed that HGF induced migration of these cells can be blocked by HSP90 inhibitors (19). Thus, in this study, we tested whether HSP90 inhibitors, such as GAs, can block the ability of GBM cells to migrate and invade.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations